A major stylar matrix polypeptide (sp41) is a member of the pathogenesis-related proteins superclass. - Ori, N (1990)
A novel stylar-specific glycosylated protein, sp41, was characterized. Sp41 constitutes greater than 12% of the transmitting tract tissue soluble proteins and is mainly localized in the extracellular matrix. Two cDNA clones corresponding to sp41 mRNA were isolated and sequenced. The decoded sequences are, respectively, 80% and 49% homologous to acidic and basic pathogen-induced (1-3)-beta-glucanases of the leaf. Thus a subfamily of (1-3)-beta-glucanase pathogenesis-related (PR) proteins constitutes one of the major stylar matrix proteins. The accumulation of sp41 transcripts in normally developing and elicitor-treated styles and leaves was followed using an RNase protection assay. During development sp41 transcript accumulation starts well after carpel differentiation. It is first detected in styles at 8 days before anthesis. The maximal level of accumulation is reached during anthesis. Elicitor-treated styles do not accumulate the leaf-type (1-3)-beta-glucanase transcript, although they retain the capacity to synthesize leaf-type pathogenesis-related proteins such as the pathogen-induced acidic chitinase. The developmental regulation of sp41 expression points to a role for them in the normal processes of flowering and reproductive physiology.